Møller polarimeter reconstruction in Hall A Jefferson Lab - Pomatsalyuk, R.I.; Vereshchaka, V.V.; Glamazdin, A.V. (Вопросы атомной науки и техники, 2013)
The Møller polarimeter reconstruction for measuring of the electron beam polarization with energies up to 11 GeV has been performed in Hall A Thomas Jefferson Laboratory (United States). This paper describes the elements of the Møller polarimeter and accelerator beamline that have been changed. The structure and characteristics of the modified data acquisition system of the polarimeter are shown. An analysis of components of systematic error of beam polarization measurement for two types of used targets is presented. В лаборатории им. Т. Джефферсона (США) проведена реконструкция мёллеровского поляриметра зала А для обеспечения измерений поляризации пучка электронов с энергией до 11 ГэВ. В работе описаны элементы мёллеровского поляриметра и электронопровода ускорителя, которые были изменены. Приведены структура и характеристики модифицированной системы сбора данных поляриметра. Проведён анализ величины систематической ошибки измерения поляризации пучка для двух типов используемых мишеней. У лабораторії ім. Т. Джефферсона (США) проведено реконструкцію мьоллерівського поляриметра залу А для забезпечення вимірювань поляризації пучка електронів з енергією до 11 ГеВ. У роботі описані елементи мьоллерівського поляриметра та електронопровода прискорювача, які були змінені. Наведено структуру та характеристики модифікованої системи збору даних поляриметра. Проведено аналіз величини систематичної помилки вимірювання поляризації пучка для двох типів мішеней, що використовувались.